2014
DOI: 10.1007/s00432-014-1864-3
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-induced killer (CIK) cells in cancer immunotherapy: report of the international registry on CIK cells (IRCC)

Abstract: Due to their easy availability and potent antitumor activity, CIK cells emerged as a promising immunotherapy approach in oncology and may gain major importance on the prognosis of cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
105
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(105 citation statements)
references
References 60 publications
0
105
0
Order By: Relevance
“…CD3 + CD8 + T cells play an essential role in the immune response against cancers (30). CD3 + CD56 + T cells are a subset of type II NKT cells with non-major histo compatibility complex-restricted tumor-killing activity (20,31). Collectively, these findings revealed that DC-CIKs were more effective as antitumor agents than CIKs.…”
Section: Discussionmentioning
confidence: 99%
“…CD3 + CD8 + T cells play an essential role in the immune response against cancers (30). CD3 + CD56 + T cells are a subset of type II NKT cells with non-major histo compatibility complex-restricted tumor-killing activity (20,31). Collectively, these findings revealed that DC-CIKs were more effective as antitumor agents than CIKs.…”
Section: Discussionmentioning
confidence: 99%
“…Fever (1), arrest of bone-marrow, gastrointestinal reactions, peripheral neurotoxicity DcRen2013B (Ren et al, 2013) Vomiting (1), diarrhea (1), hepatic complications (2) Neuritis (1), vomiting (9), diarrhea (12), hepatic complications (4) DcYuan2013L (Yuan et al, 2013) Anemia, skin petechiae, fatigue, oral pain, constipation, peripheral neuropathy Fever, anemia, skin petechiae, fatigue, oral pain, constipation, peripheral neuropathy DcNi2013B (Ni et al, 2013) None Fever (3) DcGao2014G (Gao et al, 2014) None Fever (9) None: no adverse effects and reporting standards, which will benefit patients on condition that there is more registration (Schmeel et al, 2014). Meta-analysis is an optimal choice to analyze dozens of clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…There are now over 45 studies present in the database reported on 22 different tumor entities altogether enrolling around 3,000 patients. CIK cells have gained major strides as a promising immunotherapy platform in oncology (Schmeel et al, 2015).…”
Section: The International Registry On Cik Cells (Ircc)mentioning
confidence: 99%